2021
DOI: 10.3390/biomedicines9080992
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Bee Venom-Derived Phospholipase A2 against Cholestatic Liver Disease in Mice

Abstract: Hepatocyte apoptosis and inflammation play important roles in cholestatic liver diseases. Bee venom-derived secretory phospholipase A2 (bvPLA2) has been shown to ameliorate various inflammatory diseases. However, whether bvPLA2 has a therapeutic effect against cholestatic liver disease has not been evaluated. Therefore, we investigated the effects of bvPLA2 on cholestatic liver injury and fibrosis in a murine model of 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) diet feeding. The administration of bvPLA2 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
7
1
1
Order By: Relevance
“…IHC staining with an antibody against F4/80, a macrophage marker [ 33 ], also revealed that LPS injection increased the number of F4/80-positive cells in kidney tissues, which was significantly alleviated by hispidulin administration (LPS, 7.8 ± 1.3 vs. LPS + His, 2.4 ± 0.5, p < 0.001; Figure 8 A,B).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…IHC staining with an antibody against F4/80, a macrophage marker [ 33 ], also revealed that LPS injection increased the number of F4/80-positive cells in kidney tissues, which was significantly alleviated by hispidulin administration (LPS, 7.8 ± 1.3 vs. LPS + His, 2.4 ± 0.5, p < 0.001; Figure 8 A,B).…”
Section: Resultsmentioning
confidence: 95%
“…While Ly6B.2 is expressed mainly on neutrophils, F4/80 is found primarily on macrophages. The infiltration of Ly6B.2-positive or F4/80-positive cells into the damaged tissue has been shown to be increased in various inflammatory diseases, such as postoperative ileus [ 32 ], cisplatin-induced renal injury [ 28 , 31 ], cholestatic liver disease [ 33 , 37 ], nonalcoholic fatty liver disease [ 44 ], and atherosclerosis [ 45 ]. Neutrophils and macrophages may exacerbate the LPS-induced inflammatory responses [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, phosphorylated forms of nuclear factor-κB (NF-κB) p65 and signal transducer and activator of transcription 3 (STAT3) were increased after LPS injection, which was inhibited by carnosic acid (p < 0.05; Figure 4C-E). Neutrophil infiltration was evaluated by detecting cells stained with Ly6B.2, a neutrophil marker [22]. The number of Ly6B.2-positive cells was higher in the LPS group than in the control group (Figure 5A,B).…”
Section: Carnosic Acid Attenuated Lps-induced Inflammatory Responsesmentioning
confidence: 98%
“…Investigators reported that BV group III sPLA 2 can stop the inflammation and death of nerve cells caused by prion protein fragment 106-126 ( Hossen et al, 2017a , Hossen et al, 2017b ). New research show that the treatment with phospholipase A2 significantly cured cholestatic liver injury in mice via the obstruction of inflammation and liver cell apoptosis ( Kim et al, 2021 ). The BV constituent called MCD peptide is composed of 22 amino acids having 2 disulfide bridges and possesses anti - inflammatory potential ( Bellik, 2015 , Komi et al, 2018 ).…”
Section: Pharmacological Properties Of Honey Bee Venommentioning
confidence: 99%